Strengthening Student Employability Through Applicant Tracking System-Based CV Compilation Training - Hardiansyah Hardiansyah; Rabiatul Adhawiyah; Dian Dwi Nur Rahmah; Edoardo Tondang; Diana Diana (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
Increasingly competitive job markets require students to possess strong work skills, including the ability to prepare an Applicant Tracking System (ATS)-based CV. However, some students still lack a grasp of CV standards that align with modern recruitment systems. This community service activity aims to improve students' work skills through ATS-based CV preparation training. The method used was an interactive workshop for 32 fourth- and sixth-semester psychology students, covering employment topics, ATS concepts, CV preparation practices, and mentoring. Evaluation was conducted through pre- and post-tests using an employment scale and an ATS CV knowledge questionnaire. Results showed a 55.17% increase in work skills (from 58 to 90) and a 56.67% increase in CV preparation knowledge and skills (from 60 to 94). These findings demonstrate that practice-based training is effective in improving students' work readiness and is relevant to today's digital recruitment needs.Persaingan kerja yang semakin sulit menuntut mahasiswa memiliki employability yang baik, termasuk kemampuan menyusun CV berbasis Applicant Tracking System (ATS). Namun, sebagian mahasiswa masih belum memahami standar CV yang sesuai dengan sistem rekrutmen modern. Kegiatan pengabdian ini bertujuan untuk meningkatkan employability mahasiswa melalui pelatihan penyusunan CV berbasis ATS. Metode yang digunakan adalah workshop interaktif kepada 32 mahasiswa psikologi semester 4 dan 6, yang mencakup materi employability, konsep ATS, praktik penyusunan CV, serta pendampingan. Evaluasi dilakukan melalui pre-test dan post-test menggunakan skala employability dan kuesioner pengetahuan CV ATS. Hasil menunjukkan peningkatan employability sebesar 55,17% (skor 58 menjadi 90) dan peningkatan pengetahuan serta keterampilan penyusunan CV sebesar 56,67% (skor 60 menjadi 94). Temuan ini menunjukkan bahwa pelatihan berbasis praktik efektif dalam meningkatkan kesiapan kerja mahasiswa dan relevan dengan kebutuhan rekrutmen digital saat ini.